HUBUNGAN ASUPAN PROTEIN DAN ZAT BESI DENGAN KADAR HEMOGLOBIN - Nopiana, Nopiana (JURNAL MEDIA KESEHATAN, 2015)
Diets of adolescents who always skip breakfast and lunch trigger nutritional problemsin adolescence. Young women is one of the vulnerable groups that suffer from anemia. NutritionalStudies Program student DIII an example adolescent groups and also further prospectivehealth workers who would not be exposed to nutritional problems, but based on a preliminarysurvey still found in hemoglobin levels below normal, the intake of protein and iron are also low.The purpose of this study was to determine the relationship of the intake of protein and iron inhemoglobin of Diploma Studies Student Nutrition Program MoH Bengkulu polytechnic 2014.The design of this cross-sectional study with random sampling method on 75 female students.The results showed no significant relationship between protein intake with hemoglobin levels (p= 0.005), in addition there is a relationship intake of iron with hemoglobin levels (p = 0.002). Theintake of protein and iron associated with hemoglobin levels significantly.